Sistem Informasi Penjualan Online Pada Toko Gandaria Jambi - Veronica, Veronica; Mulyono , Herry (LPPM Universitas Dinamika Bangsa, 2022)
Gandaria Jambi shop is a shop engaged in the sale of plastic and cake ingredients, in this Gandaria Jambi shop the obstacles experienced are a decrease in sales turnover due to a conventional sales system, customers have to come directly to the store to purchase products and promote products only by word of mouth. Then an Online Sales Information System was designed at the Gandaria Jambi Store with the aim of helping increase sales at the Gandaria Jambi Store and making it easier to market products. In this study using prototype modeling and it is hoped that the results of the research will make it easier for customers to make purchases, order and confirm payments and for the store to have an online sales plan that can assist in sales transactions to be more effective in doing business. In the future, the analysis and design of this online sales information system can be developed such as the feature of submitting and returning goods from shoppers at Gandaria Jambi Shop